Impact of heart myxoma localization upon its clinical course and outcome - Rafajlovski Sašo; Ilić Radoje; Gligić Branko; Kanjuh Vladimir; Tatić Vujadin; Ristić Anđelka; Obradović Slobodan; Dinčić Dragan; Ratković Nenad; Romanović Radoslav; Karić Jasna; Đenić Nemanja; et al. (Vojnosanitetski Pregled)
Introduction. Primary heart tumors are very rare. They can be benign and malignant. Benign ones make about two thirds of all heart tumors. However, they are benign only by their biologic characteristics, but potentially malignant by their localization. About three forths of benign tumors are myxomas. Their growth is usually slow and they can be for a long time silent, particularly if they do not compromise vital functional parts of the heart. Myxomas grow in the atria, mostly in the left one and very rarely in the ventricles. Case report. We presented two patients with myxomas in the left, and, in the right atrium which are representative samples of the most common localization of heart myxoma considering previous knowledge of these tumors. Analysis of the clinical course in the two presented patients with characteristic localizations showed general characteristics of the clinical course of heart myxoma. The patients did not have characteristic symptoms for a rather long period of time and the findings obtained by standard examinations did not raise suspicion of heart tumor. Pulmonary symptomatology in one patient and cardial in the other, when tumor had already occupied almost the entire atrium, suggested necessity of cardiologic examination. Indication for operation was in both patients confirmed after performed echocardiography, computed tomography of the thorax and angiography with ventriculography. The size of the removed atrial tumors and their localization explained some of the patients' troubles, but it was also amazing that they had not caused more serious problems. Operation as the only method of treatment was successful in both female patients and its effect was permanent. At annual controls neither recurrence of the tumor nor troubles possibly associated with it were observed. Conclusion. Patients with heart myxoma usually pass through asymptomatic or oligosymptomatic phase, but when troubles become manifested, they do not much differ from those due to other causes. For this reason this tumor can be diagnosed just when complications caused by its localization and growth develop. Modern cardiologic diagnostics, primarily preventive non-invasive echocardiography, enables timely diagnosis and removal of the tumor because only then it may take a name benign tumor.